Solid-state electrolyte membrane, solid-state battery and electric device
By growing sulfide solid electrolytes in situ on the surface of the fiber wire, forming a three-dimensional electrolyte skeleton, the short circuit and poor mechanical properties caused by the small thickness of the solid electrolyte film are solved, the combination of high ionic conductivity and mechanical properties is achieved, and the solid state is improved Overall performance of the battery.
Patent Information
- Application Number
- CN202411451465.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-31
AI Technical Summary
The solid electrolyte film is prone to short circuits when it is small in thickness, and its mechanical properties are poor and its ionic conductivity are small, which limits its application range.
A solid electrolyte membrane with a three-dimensional electrolyte framework and polymer is used to grow sulfide solid electrolyte in situ on the surface of the fiber wire to form a film with excellent mechanical properties and good ionic conductivity, and the thickness can be reduced to 10μm, reducing the risk of short circuit.
The air stability and mechanical properties of the solid electrolyte membrane are improved, the high capacity and excellent cycling performance of the solid state battery are ensured, short circuit phenomenon is avoided, and electrochemical performance and energy density are improved.
Smart Images

Figure BDA0005090024940000111 
Figure BDA0005090024940000121 
Figure BDA0005090024940000122
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular to a solid electrolyte membrane, a solid battery and an electrical device. Background Art
[0002] The sulfide solid electrolyte prepared by the solid phase method has a large particle size and poor uniformity, which makes it difficult to make the prepared sulfide solid electrolyte membrane thinner, usually greater than 150μm, thus severely limiting its application range. The sulfide solid electrolyte prepared by the wet method has better uniformity and smaller particle size, so it can prepare a solid electrolyte membrane less than 50μm. However, the wet method relies too much on the binder content to improve the mechanical properties of the solid electrolyte membrane to avoid the risk of lithium dendrite piercing. The increase in the binder content will hinder ion conduction, thereby reducing ionic conductivity. Summary of the invention
[0003] The purpose of the present application is to solve the problems of short circuit phenomenon, poor mechanical properties and low ion conductivity when the thickness of the solid electrolyte membrane is small, and to provide a solid electrolyte membrane, solid-state battery and electrical device with excellent mechanical properties, good ion conductivity and a thickness as low as 10μm, which can reduce the occurrence of short circuit when used in the preparation of solid-state batteries.
[0004] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a solid electrolyte membrane, the solid electrolyte membrane comprising a three-dimensional electrolyte skeleton and a polymer, the three-dimensional electrolyte skeleton comprising fiber filaments and a sulfide solid electrolyte on the surface of the fiber filaments;
[0005] The solid electrolyte membrane satisfies: A1-A2≤0.4 and A1≥1.5;
[0006] Wherein, A1 mS / cm is the ionic conductivity of the solid electrolyte membrane at 25°C, water content <0.1ppm, oxygen content <0.1ppm for 60min;
[0007] A2 mS / cm is the ionic conductivity of the solid electrolyte membrane at 25°C and 50% relative humidity for 60 min.
[0008] As an embodiment of the present application, the mass ratio of the fiber filaments to the sulfide solid electrolyte is (3-7): (3-7).
[0009] As an implementation scheme of the present application, it is characterized in that the mass ratio of the three-dimensional electrolyte skeleton and the polymer is (70-85): (15-30).
[0010] As an embodiment of the present application, the fiber filaments include at least one of lignin, cellulose, kraft lignin, modified lignin treated with an organic solvent, modified lignin after hydrolysis, and modified lignin after pyrolysis.
[0011] As an embodiment of the present application, the average diameter of the fiber filaments is 0.5 to 20 μm.
[0012] As an embodiment of the present application, the sulfide solid electrolyte includes Li 6 PS 4.5 Cl 1.5 , Li 6 PS 5 Cl, Li 3 PS 4 , Li 7 P 3 S 11 , Li 2 P 2 S 5 At least one of .
[0013] As an embodiment of the present application, the polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, and polyacrylonitrile.
[0014] As an embodiment of the present application, the viscosity average molecular weight of the polymer is 100,000 to 600,000.
[0015] As an embodiment of the present application, the thickness of the solid electrolyte membrane is 10 to 40 μm.
[0016] In a second aspect of the present application, the present application provides a solid-state battery, comprising a positive electrode, a negative electrode and the solid-state electrolyte membrane described in the present application.
[0017] In a third aspect of the present application, the present application provides an electrical device comprising the solid-state battery described in the present application.
[0018] Compared with the prior art, the beneficial effects of this application are:
[0019] The solid electrolyte membrane provided by the present application is formed by introducing a three-dimensional electrolyte skeleton of a sulfide solid electrolyte on the surface of the fiber filaments. On the one hand, the sulfide solid electrolyte is anchored on the fiber filaments by in-situ growth, which can reduce the active sites that react with water in the air; on the other hand, in the preparation of the solid electrolyte membrane, the sulfide solid electrolyte is wrapped inside the fiber formed by the fiber filaments, further reducing the probability of contact with the air; effectively improving the air stability of the solid electrolyte membrane. At the same time, the present application can further ensure the air stability of the solid electrolyte membrane by limiting the solid electrolyte membrane to meet the ionic conductivity range and difference range under different conditions. In addition, the fiber filaments are introduced into the solid electrolyte membrane as part of the three-dimensional electrolyte skeleton, which can effectively improve the mechanical properties of the solid electrolyte membrane. When the solid electrolyte membrane is subsequently applied to the preparation of a solid-state battery, the resulting solid-state battery has a high capacity and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM observation image of the three-dimensional electrolyte skeleton precursor prepared in Example 1;
[0021] Figure 2 This is a SEM observation image of the solid electrolyte membrane prepared in Example 1. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0023] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0024] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0025] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0026] In one embodiment of the present application, the present application provides a solid electrolyte membrane, the solid electrolyte membrane comprising a three-dimensional electrolyte skeleton and a polymer, the three-dimensional electrolyte skeleton comprising fiber filaments and a sulfide solid electrolyte on the surface of the fiber filaments;
[0027] The solid electrolyte membrane satisfies: A1-A2≤0.4 and A1≥1.5;
[0028] Wherein, A1 mS / cm is the ionic conductivity of the solid electrolyte membrane at 25°C, water content <0.1ppm, oxygen content <0.1ppm for 60min;
[0029] A2 mS / cm is the ionic conductivity of the solid electrolyte membrane at 25°C and 50% relative humidity for 60 min.
[0030] The present application has found that the solid electrolyte membrane provided by the present application forms a three-dimensional electrolyte skeleton by introducing fiber filaments and sulfide solid electrolytes on the surface of the fiber filaments. On the one hand, the sulfide solid electrolyte is anchored on the fiber filaments by in-situ growth, which can reduce the active sites that react with water in the air; on the other hand, in the preparation of the solid electrolyte membrane, the sulfide solid electrolyte is wrapped inside the fiber formed by the fiber filaments, further reducing the probability of contact with the air; effectively improving the air stability of the solid electrolyte membrane. At the same time, the present application limits the solid electrolyte membrane to a solid electrolyte membrane of 60 minutes ion conductivity ≥ 1.5mS / cm under an environment of 25°C, water content <0.1ppm, oxygen content <0.1ppm, and a difference of 60 minutes ion conductivity of the solid electrolyte membrane at 25°C and a relative humidity of 50% of ≤0.4mS / cm, which can further ensure the air stability of the solid electrolyte membrane on the basis of ensuring that the solid electrolyte membrane has excellent ion conductivity. In addition, the introduction of fiber filaments as part of the three-dimensional electrolyte skeleton in the solid electrolyte membrane can effectively improve the mechanical properties of the solid electrolyte membrane. When the solid electrolyte membrane is subsequently applied to the preparation of solid-state batteries, the resulting solid-state batteries have high capacity and excellent cycle performance.
[0031] It should be noted that the ionic conductivity of the solid electrolyte membrane is obtained through AC impedance testing.
[0032] Exemplarily, the ionic conductivity A1 of the solid electrolyte membrane for 60 minutes under an environment of 25°C, water content <0.1ppm, and oxygen content <0.1ppm can be any point value ≥1.5 or any two point range values, for example, it can be 1.5-2.2, or it can be 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, etc.
[0033] Exemplarily, the difference A1-A2 between the ionic conductivity A1 of the solid electrolyte membrane at 25°C, water content <0.1ppm, oxygen content <0.1ppm for 60 minutes and the ionic conductivity A2 of the solid electrolyte membrane at 25°C and relative humidity of 50% for 60 minutes can be any point value ≤0.4 or any two point range values, for example, it can be 0.1-0.4, or it can be 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, etc.
[0034] In one embodiment, the solid electrolyte satisfies: 0.1≤A1-A2≤0.4 and 1.5≤A1≤2.2.
[0035] In one embodiment, the solid electrolyte satisfies: 0.17≤A1-A2≤0.4 and 1.7≤A1≤2.1.
[0036] The research in this application found that when the solid electrolyte further satisfies 0.17≤A1-A2≤0.4 and 1.7≤A1≤2.1, the air stability of the obtained solid electrolyte is better. When used in the preparation of solid-state batteries, the obtained solid-state battery has a higher capacity and better cycle performance.
[0037] In one embodiment, the mass ratio of the fiber filaments to the sulfide solid electrolyte is (3-7): (3-7).
[0038] It should be noted that the mass of the fiber filaments is obtained by thermogravimetric testing, and the mass of the sulfide solid electrolyte is obtained by thermogravimetric testing.
[0039] Exemplarily, the mass ratio of the fiber filaments and the sulfide solid electrolyte can be any point value or any two point range values between (3-7): (3-7), such as 3:3, 3:4, 3:5, 3:6, 3:7, 4:3, 4:5, 4:6, 4:7, 5:3, 5:4, 5:6, 5:7, 6:3, 6:4, 6:5, 6:7, 7:3, 7:4, 7:5, 7:6, etc.
[0040] In one embodiment, the mass ratio of the fiber filaments to the sulfide solid electrolyte is (3-5):6.
[0041] The present application has found that when the mass ratio of the fiber filaments and the sulfide solid electrolyte is within the range given in the present application, especially when the mass ratio of the fiber filaments and the sulfide solid electrolyte is (3-5):6, a good balance between ionic conductivity and mechanical properties can be achieved, thereby effectively realizing the excellent capacity and cycle performance of the solid-state battery.
[0042] In one embodiment, the mass ratio of the three-dimensional electrolyte skeleton to the polymer is (70-85): (15-30).
[0043] It should be noted that the mass of the three-dimensional electrolyte skeleton is obtained by thermogravimetric testing, and the mass of the polymer is obtained by thermogravimetric testing.
[0044] Exemplarily, the mass ratio of the three-dimensional electrolyte skeleton and the polymer can be any point value between (70-85):(15-30) or any two point range values, such as 70:15, 70:20, 70:25, 70:30, 75:15, 75:20, 75:25, 75:30, 80:15, 80:20, 80:25, 80:30, 85:15, 85:20, 85:25, 85:30, etc.
[0045] In one embodiment, the mass ratio of the three-dimensional electrolyte skeleton to the polymer is (70-75):30.
[0046] The present application has found that the mass ratio of the three-dimensional electrolyte skeleton and the polymer will not only affect the mechanical properties of the solid electrolyte membrane, but also its ionic conductivity. When the mass ratio of the three-dimensional electrolyte skeleton and the polymer is further selected within the range given in the present application, especially (70-75):30, when the obtained solid electrolyte membrane is used in the preparation of solid-state batteries, the solid-state batteries have higher capacity and better cycle performance.
[0047] In one embodiment, the fiber filaments include at least one of lignin, cellulose, kraft lignin, modified lignin treated with an organic solvent, modified lignin after hydrolysis, and modified lignin after pyrolysis.
[0048] It should be noted that the kraft lignin is obtained by digesting lignin in sulfite or sulfate; the modified lignin treated with an organic solvent is obtained by treating with acetic acid or an ether organic solvent; the hydrolyzed modified lignin is obtained by hydrolyzing with an alkaline solvent such as sodium hydroxide; the pyrolyzed modified lignin is obtained by treating at a temperature of 600-800°C at 45-55°C / min for 5-8h. The present application does not particularly limit the treatment methods of kraft lignin, modified lignin treated with an organic solvent, modified lignin after hydrolysis, and modified lignin after pyrolysis, and any conventionally available method or commercially available method can be used.
[0049] In one embodiment, the average diameter of the fiber filaments is 0.5-20 μm.
[0050] It should be noted that the average diameter of the fiber filaments is obtained by scanning electron microscopy.
[0051] Exemplarily, the average diameter of the fiber filaments may be any point value or any two point range values between 0.5 and 20 μm, such as 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc.
[0052] In one embodiment, the average diameter of the fiber filaments is 1-10 μm.
[0053] The research in this application found that the average diameter of the fiber filaments not only affects the difficulty of in-situ growth of the sulfide solid electrolyte on the surface of the fiber filaments, but also affects the mechanical properties of the prepared solid electrolyte membrane, and at the same time affects the ionic conductivity of the solid electrolyte membrane. When the average diameter of the fiber filaments is further selected to be 0.5 to 20 μm, especially 1 to 10 μm, the comprehensive performance of the obtained solid electrolyte membrane is better, and the corresponding prepared solid-state battery has a higher capacity and a longer cycle life.
[0054] In one embodiment, the sulfide solid electrolyte includes Li 6 PS 4.5 Cl 1.5 , Li 6 PS 5 Cl, Li 3 PS 4 , Li 7 P 3 S 11 , Li 2 P 2 S 5 At least one of .
[0055] In one embodiment, the polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, and polyacrylonitrile.
[0056] In one embodiment, the viscosity average molecular weight of the polymer is 100,000 to 600,000.
[0057] It should be noted that the viscosity average molecular weight of the polymer is obtained by testing using a dilute solution viscosity method.
[0058] Exemplarily, the viscosity-average molecular weight of the polymer may be any point value between 100,000 and 600,000 or any two points in the range, such as 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, etc.
[0059] In one embodiment, the viscosity average molecular weight of the polymer is 300,000 to 400,000.
[0060] The present application study found that the type of polymer and the viscosity-average molecular weight will have a certain influence on the mechanical properties of the solid electrolyte membrane, and will also affect the complexing effect with the three-dimensional electrolyte skeleton, thereby affecting the air stability of the solid electrolyte membrane. When the viscosity-average molecular weight of the polymer is further selected to be 100,000 to 600,000, especially 300,000 to 400,000, the obtained solid electrolyte membrane has a better overall performance of the solid-state battery prepared accordingly.
[0061] In one embodiment, the solid electrolyte membrane has a thickness of 10-40 μm.
[0062] It should be noted that the thickness of the solid electrolyte membrane is obtained by testing with a thickness gauge.
[0063] Exemplarily, the thickness of the solid electrolyte membrane may be any point value or any two point range value between 10 and 40 μm, such as 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc.
[0064] In one embodiment, the thickness of the solid electrolyte membrane is 12-20 μm.
[0065] The present application has found that the technical solution of the present application can be used to obtain a solid electrolyte membrane with a thickness within an appropriate range, specifically 10 to 40 μm, that is, the thickness of the solid electrolyte membrane provided by the present application can be reduced to 10 μm and still achieve excellent comprehensive effects. On the one hand, since the introduction of fiber filaments can improve the mechanical properties of the solid electrolyte membrane while avoiding the decrease in ionic conductivity, the electrochemical performance and energy density of the corresponding solid-state battery can be improved, and the transfer impedance between the electrolyte particles in the solid-state battery can be reduced. Therefore, when the thickness of the solid electrolyte membrane is reduced to 10 μm, the solid-state battery prepared will not short-circuit. On the other hand, when the upper limit of the thickness of the solid electrolyte membrane is further selected to be 40 μm, the battery life caused by poor heat dissipation due to excessive thickness of the membrane can be avoided. When the thickness of the solid electrolyte membrane is further selected to be 12 to 20 μm, the comprehensive performance of the corresponding solid-state battery is better.
[0066] In one embodiment, the density of the solid electrolyte membrane is greater than 1.5 g / cm 3 , porosity <15%.
[0067] It should be noted that the density of the solid electrolyte membrane is obtained by weighing and using the formula ε = m 膜 / V 膜 The porosity is calculated by density method and using the formula ε = V 孔 / V 膜外观 =(V 膜外观 -V 膜骨架 ) / V 膜外观 =(ρ 膜表观 -ρ 膜材料 ) / ρ 膜表观 Calculated;
[0068] In the density formula, m 膜 Represents the weight of the solid electrolyte membrane, V 膜 Represents the volume of the solid electrolyte membrane (i.e., the product of the area and thickness of the electrolyte membrane); in the porosity formula, V 孔 Represents the volume of the pores in the solid electrolyte membrane, that is, the volume of the solid electrolyte membrane V 膜外观 The volume V of the solid electrolyte membrane skeleton 膜骨架 The difference, ρ 膜表观 represents the density of the electrolyte membrane obtained by weighing method, ρ 膜材料 Represents the density of the membrane raw material.
[0069] In one embodiment, the method for preparing the solid electrolyte membrane comprises the following steps:
[0070] (1) adding a sulfide solid electrolyte precursor and pretreated fiber filaments to an organic solvent and stirring the mixture for reaction, and heating to remove the organic solvent after the stirring reaction to obtain a powder; and then vacuum annealing the powder to obtain a three-dimensional electrolyte skeleton precursor;
[0071] (2) The three-dimensional electrolyte skeleton precursor and the polymer are mixed and extruded, and then subjected to static pressure treatment to obtain a solid electrolyte membrane.
[0072] In one embodiment, the sulfide solid electrolyte precursor includes at least two of lithium sulfide, phosphorus pentasulfide, lithium hydroxide, lithium carbonate, and lithium chloride. In one embodiment, in step (1), the organic solvent includes at least one of tetrahydrofuran, anhydrous acetonitrile, and anhydrous ethanol.
[0073] In one embodiment, in step (1), the stirring reaction time is 20-40 hours.
[0074] In one embodiment, in step (1), the annealing treatment is performed at a temperature of 500-600° C. and for a time of 3-9 hours.
[0075] In one embodiment, in step (1), the pretreatment of the fiber filaments is: desalting the fiber filaments until the salt concentration is less than 1000 ppm and then drying them.
[0076] In one embodiment, in the step (2), the extrusion temperature is 150-200° C. and the rotation speed is 400-800 rpm.
[0077] In one embodiment, in step (2), the pressure of the static pressure treatment is 450-550 MPa.
[0078] The research of the present application found that the preparation method provided in the present application can effectively make the fiber filaments and the sulfide solid electrolyte grown in situ on the surface of the fiber filaments form a three-dimensional electrolyte skeleton precursor. Specifically, the fiber filaments are entangled to form a network structure and construct a three-dimensional ion channel, which can improve the mechanical properties of the solid electrolyte membrane while ensuring good ionic conductivity.
[0079] In one embodiment of the present application, the present application provides a solid-state battery, comprising a positive electrode, a negative electrode and the solid electrolyte membrane described in the present application.
[0080] The present application has no special requirements for the positive electrode and negative electrode of the solid-state battery, and any positive electrode and negative electrode conventionally used in the present invention can be selected.
[0081] In one embodiment of the present application, the present application provides an electrical device, including the solid-state battery described in the present application.
[0082] Example 1
[0083] The present invention provides a solid electrolyte membrane and a solid battery. The preparation method of the solid electrolyte membrane and the solid battery comprises the following steps:
[0084] (1) Preparation of solid electrolyte membrane
[0085] S1. Digest lignin in sodium sulfite for 5 hours to obtain sulfate lignin; then wash the sulfate lignin repeatedly with water, and wash with hydrochloric acid to keep the pH <5 to remove the ash in the lignin. When the salt concentration is detected to be <1000ppm, the washing is terminated, and the mixture is dried in a vacuum oven at 100°C to obtain pretreated sulfate lignin (with an average diameter of 5 μm);
[0086] S2. Li 2 S and lithium chloride were dissolved in anhydrous ethanol at a molar ratio of 1:1 to form a uniform solution for later use; 2 S.P. 2 S 5 The treated kraft lignin was dissolved in THF solvent and stirred for 24 h, thereby in situ growing β-Li on the kraft lignin fibers. 3 PS 4 ·3THF, followed by Li 2 S and lithium chloride anhydrous ethanol solution were added and stirred for 12 hours, and then the solvent was evaporated at 90°C to obtain a light yellow powder; the light yellow powder was annealed at 550°C in vacuum for 6 hours to obtain a three-dimensional electrolyte skeleton precursor, that is, a sulfide solid electrolyte Li grown on the surface of the kraft lignin fiber. 6 PS 4.5 Cl 1.5 Among them, the kraft lignin fiber and the sulfide solid electrolyte Li 6 PS 4.5 Cl 1.5 The mass ratio of is 4:6; SEM observation of the three-dimensional electrolyte skeleton precursor is carried out, and the results are as follows Figure 1 As shown, from Figure 1 It can be seen that the sulfide solid electrolyte grows in situ on the surface of the kraft lignin fiber;
[0087] S3, the three-dimensional electrolyte skeleton precursor and polyethylene oxide (viscosity average molecular weight of 350,000) were mixed at a mass ratio of 70:30 for 5 minutes, and melt extruded and spun using a screw extruder; then, it was subjected to static pressure treatment at 500MPa to obtain a solid electrolyte membrane with a thickness of 20μm; the solid electrolyte membrane was observed by SEM, and the results were as follows Figure 2 As shown;
[0088] (2) Preparation of solid-state batteries
[0089] 1) Preparation of solid-state battery S1
[0090] The positive electrode uses NCM811, LPSCl, VGCF, and PTFE in a ratio of 80:15:4.5:0.5, and is rolled into a positive electrode film several times by a dry preparation method, and a 10 mm round piece is cut for use; the silicon-carbon negative electrode, LPSCl, VGCF, and PTFE are mixed in a pot mill in a mass ratio of 70:28:1.5:0.5, and then rolled several times to obtain a negative electrode film, and a 10 mm round piece is cut for use; the solid electrolyte membrane 1 (a solid electrolyte membrane prepared by placing the solid electrolyte membrane at 25°C, a water content of <0.1ppm, and an oxygen content of <0.1ppm for 60 minutes) is cut into 10 mm round pieces; the negative electrode-electrolyte membrane-positive electrode are placed in the mold battery PEEK sleeve in sequence, and assembled at a pressure of 360MPa for testing;
[0091] 2) Preparation of solid-state battery S2
[0092] The preparation process is the same as that of solid-state battery S1, wherein solid-state electrolyte membrane 1 is replaced by solid-state electrolyte membrane 2 (a solid-state electrolyte membrane obtained by placing the prepared solid-state electrolyte membrane in an environment of 25° C. and a relative humidity of 50% for 60 minutes).
[0093] Embodiments 2 to 4
[0094] The embodiment of the present application provides a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Example 1 lies in that the thickness of the prepared solid electrolyte membrane is adjusted to achieve the parameters in Tables 1 and 2.
[0095] Embodiments 5 to 8
[0096] The embodiment of the present application provides a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Example 1 lies in adjusting the mass ratio of the three-dimensional electrolyte skeleton and the polymer to achieve the parameters in Tables 1 and 2.
[0097] Examples 9 to 12
[0098] The embodiments of the present application provide a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Embodiment 1 lies in adjusting the mass ratio of the fiber filaments and the sulfide solid electrolyte to achieve the parameters in Tables 1 and 2.
[0099] Embodiment 13
[0100] The embodiment of the present application provides a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Example 1 lies in that the type of sulfide solid electrolyte is changed to achieve the parameters in Table 1 and Table 2.
[0101] Embodiments 14 to 16
[0102] The embodiments of the present application provide a solid electrolyte membrane and a solid-state battery. The difference between the preparation methods of the solid electrolyte membrane and the solid-state battery and those of Embodiment 1 lies in that the type of polymer or the viscosity-average molecular weight is changed to achieve the parameters in Table 1 and Table 2.
[0103] Examples 17 to 20
[0104] The embodiments of the present application provide a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Embodiment 1 lies in that the average diameter of the fiber filaments is changed to achieve the parameters in Tables 1 and 2.
[0105] Embodiment 21
[0106] The embodiments of the present application provide a solid electrolyte membrane and a solid-state battery. The difference between the preparation methods of the solid electrolyte membrane and the solid-state battery and those of Embodiment 1 lies in that the type of fiber filaments is changed to achieve the parameters in Tables 1 and 2.
[0107] Comparative Example 1
[0108] The comparative example of the present application provides a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Example 1 is that no fiber filaments are added to achieve the parameters in Tables 1 and 2.
[0109] Comparative Examples 2-3
[0110] The comparative example of the present application provides a solid electrolyte membrane and a solid-state battery. The difference between the preparation method of the solid electrolyte membrane and the solid-state battery and that of Example 1 lies in that the mass ratio of the fiber filaments and the sulfide solid electrolyte is changed to achieve the parameters in Tables 1 and 2.
[0111] The types of fiber filaments, sulfide solid electrolytes and polymers used in the embodiments and comparative examples, the mass ratio M1 of fiber filaments and sulfide solid electrolytes, the mass ratio M2 of three-dimensional electrolyte skeletons and polymers, the average diameter of fiber filaments, the viscosity-average molecular weight of polymers, the thickness of solid electrolyte membranes, and the parameters of A1 and A2 are shown in Tables 1 and 2;
[0112] Among them, the ionic conductivity of the solid electrolyte membrane is tested by AC impedance using a Transmission Power Instrument 1260A impedance / gain-phase analyzer with a frequency range of 1MHz-0.1Hz.
[0113] Solid electrolyte membrane 1 ion conductivity test: Solid electrolyte membrane 1 (a solid electrolyte membrane prepared by placing the solid electrolyte membrane at 25°C, water content <0.1ppm, oxygen content <0.1ppm for 60min) was cut into discs with a diameter of 10mm, and carbon-coated aluminum foil was attached on both sides. The discs were placed in a mold battery PEEK sleeve, and then stainless steel columns were inserted on both sides to block the electrodes. The discs were tested under a pressure of 360MPa, and A1 was calculated as follows:
[0114] A1=I / (Re×S)
[0115] Where, I is the thickness of the sample under test (cm); Re is the body impedance of the sample under test (Ω), which can be obtained from the intersection of the semicircle arc and the oblique line in the Nyquist diagram of the electrochemical impedance spectrum obtained by the above test; S is the effective area of the electrode (cm 2 );
[0116] Solid electrolyte membrane 2 ion conductivity test: The test method is the same as solid electrolyte membrane 1, except that solid electrolyte membrane 1 is replaced by solid electrolyte membrane 2 (a solid electrolyte membrane after the prepared solid electrolyte membrane is placed in an environment of 25°C and relative humidity of 50% for 60 minutes), and A2 is calculated.
[0117] Table 1 Solid electrolyte membrane parameters
[0118]
[0119]
[0120] Table 2 Solid electrolyte membrane parameters
[0121]
[0122]
[0123] The mechanical strength of the solid electrolyte membranes prepared in the examples and comparative examples and the cycle performance and capacity test results of the solid-state batteries prepared are shown in Table 2; wherein the test method comprises the following steps:
[0124] (1) Mechanical strength of solid electrolyte membrane: The mechanical strength of the solid electrolyte membrane was tested using a universal tensile machine, specifically a universal tensile machine of model CMT4202 / ZWICK / Z020. The size of the membrane during the test was 8cm×8cm×0.2mm, the loading speed was set to 1-30mm / min, and the national standard test method was the thermoplastic elastomer method.
[0125] (2) Performance of solid-state batteries
[0126] The solid electrolyte membrane prepared in the embodiment and the comparative example was subjected to constant current charge and discharge tests at 1.9-3.7V and 0.1C (1C=200mA / g) by subjecting the solid electrolyte membrane prepared in the embodiment and the comparative example to conditions of 25°C, water content <0.1ppm and oxygen content <0.1ppm for 60min to prepare a solid-state battery S1, and the solid-state battery prepared in the conditions of 25°C and relative humidity of 50% for 60min to prepare a solid-state battery S2. The two groups of solid-state batteries corresponding to the embodiment and the comparative example were subjected to constant current charge and discharge tests at 1.9-3.7V and 0.1C (1C=200mA / g), and the initial discharge specific capacity and the capacity retention rate after 100 cycles were calculated.
[0127] Table 3 Solid-state battery performance test
[0128]
[0129]
[0130] It can be seen from Table 3 that when the technical solution provided by the present application is adopted, the obtained solid electrolyte membrane has high mechanical strength, and the corresponding prepared solid-state battery has high capacity and excellent cycle performance; specifically, the obtained solid-state battery S1 has a first discharge specific capacity of more than 193.21 mAh / g, and a capacity retention rate of more than 87.2% after 100 cycles, and the first discharge specific capacity of the solid-state battery S2 is more than 191.92 mAh / g, and a capacity retention rate of more than 87.0% after 100 cycles. The difference between the first discharge specific capacities of the solid-state battery S1 and the solid-state battery S2 is less than 4.99 mAh / g;
[0131] It can be seen from Examples 1 to 21 and Comparative Example 1 that when fiber filaments are not introduced, the obtained solid electrolyte membrane will short-circuit when the thickness is 20 μm; it can be seen from Examples 1 to 21 and Comparative Examples 2 to 3 that when the value of A1 or A1-A2 of the solid electrolyte membrane is not within the range given in the present application, the comprehensive performance of the obtained solid-state battery cannot achieve the effect of the present application.
[0132] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane comprises a three-dimensional electrolyte skeleton and a polymer, wherein the three-dimensional electrolyte skeleton comprises fiber filaments and a sulfide solid electrolyte on the surface of the fiber filaments; The solid electrolyte membrane satisfies: A1-A2≤0.4 and A1≥1.5; Wherein, A1 mS / cm is the ionic conductivity of the solid electrolyte membrane at 25°C, water content <0.1ppm, oxygen content <0.1ppm for 60min; A2 mS / cm is the ionic conductivity of the solid electrolyte membrane at 25°C and 50% relative humidity for 60 min.
2. The solid electrolyte membrane according to claim 1, characterized in that The mass ratio of the fiber filaments to the sulfide solid electrolyte is (3-7): (3-7).
3. The solid electrolyte membrane according to claim 1, characterized in that The mass ratio of the three-dimensional electrolyte skeleton to the polymer is (70-85): (15-30).
4. The solid electrolyte membrane according to claim 1, characterized in that The fiber filaments include at least one of lignin, cellulose, sulfate lignin, modified lignin treated with an organic solvent, modified lignin after hydrolysis, and modified lignin after pyrolysis.
5. The solid electrolyte membrane according to claim 1, characterized in that The average diameter of the fiber filaments is 0.5 to 20 μm.
6. The solid electrolyte membrane according to claim 1, characterized in that The sulfide solid electrolyte includes Li6PS 4.5 Cl 1.5 、Li6PS5Cl、Li3PS4、Li7P3S 11 , at least one of Li2P2S5; And / or, the polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, and polyacrylonitrile.
7. The solid electrolyte membrane according to claim 6, characterized in that The viscosity average molecular weight of the polymer is 100,000 to 600,000.
8. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the solid electrolyte membrane is 10-40 μm.
9. A solid-state battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a solid electrolyte membrane as claimed in any one of claims 1 to 8.
10. An electrical device, characterized in that: Comprising the solid-state battery as claimed in claim 9.
Citation Information
Patent Citations
Solid electrolyte membrane, preparation method and application thereof
CN113471524A
Composite solid electrolyte membrane, preparation method thereof and all-solid-state lithium metal battery
CN114927753A
Solid electrolyte membrane and preparation method thereof
CN115241521A
Polymer solid electrolyte membrane and lithium ion battery
CN116154279A
Solid-state composite electrolyte membrane, preparation method thereof and battery
CN117613357A
